THE ROLE OF FINANCIAL RESILIENCE FACTORS ON FINANCIAL MANAGEMENT BEHAVIOR IN CENTRAL UMKM ACTORS STRAIGHT WOVEN CRAFTS IN CAWAS DISTRICT KLATEN DISTRICT - Edi Wibowo; Akbar Febrianto (Transpublika Publisher, 2025)
In the field of economics, the concept of financial management behavior is highly regarded. It encompasses all aspects of acquiring, utilizing, and managing funds within a company. The focus of this study is to examine how financial knowledge, income, financial attitudes, and personality impact the financial management behavior of MSMEs operating in lurik weaving craft centers in Cawas District, Klaten Regency. The subjects of this research were 94 MSMEs at the lurik weaving craft center in Cawas District, Klaten Regency. Various data analysis methods were utilized including multiple linear regression, t-test, F-test, and coefficient of determination. The findings of the study indicate that there is a notable impact of financial literacy on the financial management practices of micro, small, and medium enterprises (MSMEs) in the lurik weaving industry in Cawas District, Klaten Regency. The level of income plays a vital role in shaping the financial management practices of small and medium enterprises operating within the lurik weaving craft centers in Cawas District, Klaten Regency. The attitudes towards finances also play a crucial role in determining the financial management behavior of MSMEs in these areas. Additionally, the personality traits of individuals involved in running MSMEs at lurik weaving craft centers in Cawas District, Klaten Regency have a significant impact on their financial management practices.